MANAJEMEN PEMASARAN DALAM PERSPEKTIF MASLAHAH MURSALAH - Hendra Rofiullah, Ahmad; Riesty, Kurnia (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2023)
Maslahah mursalah is the path taken by Islamic law to apply its rules and commands to new events for which there is no nashnya. In addition, maslahah mursalah is also a way of determining the rules that must exist in the course of human life, in order to be in accordance with maqashid sharia ammah (maintenance of religion, soul, mind, offspring and property), and an act that is essentially to maintain the five aspects of the shara's objectives, then called maslahah. The concept of maslahah mursalah is not only limited to worship issues, but also economic issues (muamalah). In this case, the problem that will be raised in this paper is about marketing management in the perspective of maslahah mursalah. research related to marketing strategies from the perspective of maslahah mursalah. The steps that need to be carried out when using the literature study model are first, the researcher here makes observations and analyzes the phenomena that occur related to the topic of writing the article. Second, data sources come from empirical data from official documents. Third, determining the focus of research based on the literature obtained. Fourth, reviewing various sources of literature to find new ideas related to the research to be carried out. Researchers obtained data sourced from official literature relevant to the research topic such as journals, books, or scientific articles. The results of this study indicate that marketing management based on maslahah mursalah is an analysis, planning, implementation, and control of programs designed to create, build, and maintain profitable exchanges with target markets with a view to achieving the objectives of organizational goals by taking into account sharia values in the form of maslahah, justice and prioritizing the concept of grace and pleasure, both from sellers and buyers, to Allah SWT.